Diversity patterns and conservation of the Vigna spp. in Mozambique: A comprehensive study - Brilhante, Miguel; Catarino, Sílvia; Darbyshire, Iain; Bandeira, Salomão; Moldão, Margarida; Duarte, Maria Cristina; Romeiras, Maria M. (Frontiers in Ecology and Evolution, 2023)
Mozambique supports a high diversity of native legume species, including many Crop Wild Relatives (CWRs). Among them, the still understudied genus Vigna is a particularly notable and promising donor of favorable traits for crop improvement. This study aims to provide an updated overview of Vigna CWRs diversity in Mozambique, defining a conservation strategy for priority target taxa and areas. A checklist of Vigna taxa was prepared and using five criteria (taxonomic group, ethnobotanical value, global and regional distributions, and ex situ conservation status), the prioritization of each taxon was determined. There are 21 Vigna native taxa occurring in Mozambique, with the Chimanimani Mountains and Mount Gorongosa, as diversity hotspots for the genus. Following the IUCN Red List criteria, 13 taxa are of Least Concern, while the remaining eight are currently Not Evaluated. According to their priority level for further conservation actions, 24% of the taxa are of high priority, 67% of medium priority, and 9% of low priority. The important hotspot of Chimanimani Mountains is among the areas most affected by the predicted future increase in temperature and reduction of rainfall. The obtained distribution and species richness maps, represent a relevant first tool to evaluate and improve the effectiveness of Protected Areas and IPAs of Mozambique for the conservation of Vigna CWRs. The in situ gap analysis showed that 52% of the Vigna taxa are unprotected; this could be overcome by establishing reserves in Vigna diversity centers, considering the different types of habitats to which the different taxa are adapted, and by increasing in situ protection for the high priority ones. The ex situ conservation of Vigna is very limited and storing seed collections of these CWRs, is an essential component in global food security, as some taxa seem suitable as donors of genetic material to increase resistance to pests and diseases, or to drought and salinity. Overall, we provide recommendations for future research, collecting, and management, to conserve Vigna CWR in Mozambique, providing new data for their sustainable use in crop enhancement, as well as proposing measures for future conservation programs.